The impact of pine plantations and alien invertebrates on native forest and fynbos invertebrate communities in Table Mountain National Park - Uys, Charmaine Janet (Department of Biological Sciences, 2014)
While the Cape Peninsula (South Africa) is renowned for its exceptional plant and invertebrate diversity and endemism, extensive alien plant invasions and exotic pine plantations threaten and reduce native species richness. This study frames invasion ecology theory in a conservation context, and examines the impact of planting and felling pine on litter invertebrate communities, by comparing invertebrate diversity between pine plantations and native vegetation. Impacts of the worst invasive alien invertebrate (Argentine ant, Linepithema humile) and other alien invertebrate species are investigated. This is one of the first attempts to inventory and quantify impacts of non-ant alien invertebrates in Table Mountain National Park. The entire ground-dwelling invertebrate community was sampled at 31 sites in summer 2008/2009, using soil cores, leaf litter samples, pitfall traps, sugar-baited ant traps and decayed logs. A total of 112 404 individuals, representing 728 species (10 classes and 38 orders), including nine Cape Peninsula endemic and 19 alien species, was collected. Pine plantations supported lower species richness and abundance, and different community assemblages, compared to Afrotemperate forest, but similar species richness to fynbos. This supports previous local studies and global trends. Pine plantations shared fewer species with fynbos than forest, and negatively affect fynbos-specialist invertebrates, because afforestation reduced available fynbos habitat. Alien species richness was similar across habitats. Argentine ants, like most other alien species identified, were present in all habitats. The impact of Argentine ant invasion on native ant communities was evaluated using species richness and community composition analyses, species co-occurrence patterns (C-score), and the functional group approach. The comparative approach adopted provided no evidence for displacement, impoverishment, or community disassembly. No clear impacts of the 18 non-ant alien species on the abundance, species richness, or community composition of corresponding native taxa were detected. Disturbance history offers a more parsimonious explanation for the trends observed, particularly in fynbos. However, carnivorous molluscs require careful monitoring, given their abundance and known impacts elsewhere. Using a reiterative process and IndVal, two ant species (Pheidole capensis and Camponotus bertolinii) were selected as ecological indicators of restoration progress in fynbos following clear-felling of pine. Ants similarly have application for monitoring in other Mediterranean-type ecosystems impacted by invasive pines.